"A river is not a boundary": interplays of national and linguistic citizenship in Pulaar language activism. Issue 1 (2nd January 2017) - Hames, John
Abstract: This article examines the interplay of linguistic citizenship and national citizenship within a trans-border language movement. Since the late 1950s, language activists from among the Haalpulaar'en of Senegal and Mauritania have practiced forms of literacy teaching, literary production, theater and journalism in promoting their language, known as Pulaar. These activists' trans-border collaborations and their emergence from two distinct national contexts – where, in both cases, Pulaar is spoken by a minority of the population – must be understood in relation to one another. Tracing the biographical itineraries of several key activists, this article illustrates how Senegalese and Mauritanian Pulaar militants have collaborated when it comes to language promotion yet frame their grievances within their respective national political arenas. More than a form of local resistance based on trans-border linguistic and cultural ties, Pulaar language activism has emerged thanks to opportunities presented by forms of post-colonial state-building, including the creation of national radio.